Microsoft Word 2010 step by step - Cox, Joyce, 1946-; Lambert, Joan.; Safari eBooks (Redmond, Wash. : Microsoft Press, 2010)
This guide will teach you how to create impressive documents with Word 2010. Topics include using styles and themes; sharing, printing, and publishing documents; editing images from within Word; using SmartArt(reg) diagrams and charts; creating references, footnotes, indexes, and tables of contents; collaborating with multiple people at the same time on the same document; and turning your ideas into blogs, Web pages, and more.
Description based on print version record.
Includes index.
Keywords: Microsoft Word; Word processing; Electronic books